1998
DOI: 10.1002/(sici)1097-4636(199824)43:4<451::aid-jbm13>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Histological, chemical, and crystallographic analysis of four calcium phosphate cements in different rabbit osseous sites

Abstract: Four calcium phosphate cement formulations were implanted in the rabbit distal femoral metaphysis and middiaphysis. Chemical, crystallographic, and histological analyses were made at 2, 4, and 8 weeks after implantation. When implanted into the metaphysis, part of the brushite cement was converted into carbonated apatite by 2 weeks. Some of the brushite cement was removed by mononuclear macrophages prior to its conversion into apatite. Osteoclastlike cell mediated remodeling was predominant at 8 weeks after br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
125
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(148 citation statements)
references
References 15 publications
9
125
2
Order By: Relevance
“…4). The release of phosphate in conjunction with the adsorption of Ca 2+ and Mg 2+ is related to the well know tendency of brushite cements to convert into calcium phosphate phases with a higher Ca: P ratio 4447 . Surprisingly, sodium pyrophosphate and phytic acid behaved differently and expressed both Ca 2+ and phosphate ions.…”
Section: Discussionmentioning
confidence: 99%
“…4). The release of phosphate in conjunction with the adsorption of Ca 2+ and Mg 2+ is related to the well know tendency of brushite cements to convert into calcium phosphate phases with a higher Ca: P ratio 4447 . Surprisingly, sodium pyrophosphate and phytic acid behaved differently and expressed both Ca 2+ and phosphate ions.…”
Section: Discussionmentioning
confidence: 99%
“…CaP biomaterials once implanted adsorb various proteins (soluble growth factor, serum proteins, and extracellular matrix proteins) onto their surfaces which alter the interfacial properties resulting in enhanced in vivo degradation [2,56]. Brushite cements are shown to resorb at a much faster rate when compared to apatite cements [57,58,59]. This difference can be explained by the compositional difference observed for the final products of these cements.…”
Section: In Vivo Degradation and Resorption Of Calcium Phosphatesmentioning
confidence: 99%
“…Therefore, if brushite cement grafts contain large amounts of unreacted TCP then the dicalcium phosphate dehydrate (DCPD) get resorbed leaving behind long standing β-TCP material [67,92]. Another factor that limits the rate and extent of brushite resorption is the phase conversion phenomenon [57,93]. After demonstrating fast degradation post implantation, the remaining brushite cement converts to less soluble apatites (octacalcium phosphate OCP and hydroxyapatite HA) [94,95,96].…”
Section: In Vivo Degradation and Resorption Of Calcium Phosphatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of bone cements constituted of CaP phases that can be formed at room temperature (calcium deficient HA, brushite, octacalcium phosphate and monetite) opened up a wide range of possibilities in the manufacture of new CaP bone scaffold materials [1215]. Importantly, these materials have much lower solubility rates and have been shown to transform into a more stable HA phase upon implantation [1618]. In fact it has been suggested that these less crystalline phases with lower solubility than sintered CaPs have superior biological properties [19].…”
Section: Bioceramicsmentioning
confidence: 99%